2017
DOI: 10.4012/dmj.2016-298
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of zirconia-composite veneered crowns in comparison with zirconia-porcelain crowns

Abstract: The objectives were to evaluate the fracture resistance and stress concentration in zirconia/composite veneered crowns in comparison to zirconia/porcelain crowns using occlusal fracture resistance and by stress analysis using finite element analysis method. Zirconia substructures were divided into two groups based on the veneering material. A static load was applied occlusally using a ball indenter and the load to fracture was recorded in Newtons (N). The same crown design was used to create 3D crown models an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
3
23
0
1
Order By: Relevance
“…Samples of the control group of the crowns obtained by layering composite over zirconia copings (Group Z) had a mean fracture strength of 1142.3MPa when a mean load of 116.49kg was applied. The mean fracture strength of zirconia layered with composite was 1465N in a study conducted by Alsadon et al [ 4 ] and 1094 ± 206N as per a study conducted by Atout and Dawood,[ 12 ] which is comparable with the fracture strength values for zirconia-layered composite crowns in this study. Samples of the control group of the crowns obtained by layering composite over PEEK copings (Group P) had the highest mean fracture strength of 2134.64MPa when a mean load of 217.67kg was applied.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Samples of the control group of the crowns obtained by layering composite over zirconia copings (Group Z) had a mean fracture strength of 1142.3MPa when a mean load of 116.49kg was applied. The mean fracture strength of zirconia layered with composite was 1465N in a study conducted by Alsadon et al [ 4 ] and 1094 ± 206N as per a study conducted by Atout and Dawood,[ 12 ] which is comparable with the fracture strength values for zirconia-layered composite crowns in this study. Samples of the control group of the crowns obtained by layering composite over PEEK copings (Group P) had the highest mean fracture strength of 2134.64MPa when a mean load of 217.67kg was applied.…”
Section: Discussionsupporting
confidence: 87%
“…To overcome this disadvantage of ceramic, layering of composite over zirconia coping was tried, and as literature suggests, the performance in terms of fracture strength of these crowns was at par with that of zirconia ceramic crowns. [ 2 4 5 6 ] The advantage of these crowns was that it had the strength of the zirconia substructure and a resilient layering of composite. It also had the advantage of easy handling and intraoral repair.…”
Section: Introductionmentioning
confidence: 99%
“…Alghazzawi and Janowski[ 24 ] stated that pressing technique is considered technique of choice over layering on yttria-stabilized tetragonal zirconia polycrystals. Alsadon et al [ 25 ] conducted a study to show that zirconia composite crowns showed similar occlusal load bearance as compared to zirconia porcelain crowns.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior fixed restorations ought to have the capability to tolerate a 500 N occlusal load 22,23 . Accordingly a load of 500 N was applied by a ball model of diameter 5.8 mm equal to that of metallic rod ball of the universal testing machine used for fracture resistance test in this study.…”
Section: Finite Element Analysismentioning
confidence: 99%